The Effect of Eggs Shape Index on Embryo on Mortalities, Unhatched Eggs and Day Old duck Abnormalities of Selected and Control Tegal Duck - Setiadi, Priyo (ANIMAL PRODUCTION, 2000)
An experiment was conducted to study the effect of eggs shape index on embryo mortalities, unhatched egg and day old duck abnormalities of selected and control Tegal duck. A total of 1428 fertile eggs obtained from a selected duck group and a control group were divided in to 3 group according to their eggs shape index (ESI), i.e. small (ESI ,79 percent), medium ( ESI ,82 percent ) and large (ESI ,85 percent ). The ESI was measured as a ratio of wide and length of eggs and percentage. Three batches of incubation with 7 day interval were carried out as replicates. Parameter measured were embryo mortalities, number of unhatched eggs and number of abnormal day old duck. Candling of eggs were performed at 6, 14 and days of incubation and mortalities of embryo were detected by loup. Results of the experiment showed that lowest embryos mortalities was occurred on medium eggs (24 percent) and significantly ( p< 0,05 ) affected by eggs size. Abnormal DOD from medium eggs was significantly (p ,0,05 ) lower (13 percent ) than the small (23 percent ) and large (21 percent ) eggs. Similar trends on eggs from selected duck and control ducks. This may be due to short term of selection program and young age of the female duck (24 weeks ). These results conclude that medium eggs (ESI ,82 percent) were the best size for hatching eggs. (Animal Production 2(1): 25-32 (2000)Key word : duck , hatching eggs, selection, eggs shape index